ANALISIS KESULITAN BELAJAR IPA PERSERTA DIDIK KELAS 2 - wini restu; wulan munawaroh; desyi rosita (STKIP Paris Barantai, 2023)
This study aims to determine the causes of student learning diffculties in class II science at MI darul huda to determine student learning diffculties caused by the media or facilities at school, this research uses qualitative methods with descriptive studies, analytical or observastional studies and literature review methods. Review by collecting data from several sources in the form of books and journals. Using google scholar data that is collected and then managed to produce conclusions about literature review on sciensce learning students still have difficulty understanding the material provided by the teacher because there are no facilities provided at school. As students who are less able and active in learning. Penelitian Keywords: Learning Difficulties, teachers, students.